Licorice Ameliorates Cisplatin-Induced Hepatotoxicity Through Antiapoptosis, Antioxidative Stress, Anti-Inflammation, and Acceleration of Metabolism - Man, Qiong; Deng, Yi; Li, Pengjie; Ma, Jun; Yang, Zhijun; Yang, Xiujuan; Zhou, Yan; Yan, Xiao (Frontiers in Pharmacology, 2020)
Cisplatin (CP) is one of the most effective antitumor drugs in the clinic, but has serious adverse reactions, and its hepatotoxicity has not been fully investigated. Licorice (GC), a traditional herbal medicine, has been commonly used as a detoxifier for poisons and drugs, and may be an effective drug for CP-induced hepatotoxicity. However, its mechanism and the effector molecules remain ambiguous. Therefore, in this study, a network pharmacology and proteomics-based approach was established, and a panoramic view of the detoxification of GC on CP-induced hepatotoxicity was provided. The experimental results indicated that GC can recover functional indices and pathological liver injury, inhibit hepatocyte apoptosis, upregulate B-cell lymphoma/leukemia 2 (Bcl-2) and superoxide dismutase (SOD) levels, and downregulate cellular tumor antigen p53 (p53), caspase-3, malondialdehyde (MDA), high mobility group protein B1 (HMGB1), tumor necrosis factor alpha (TNF-α), and interleukin 1β (IL-1β) levels. Proteomics indicated that GC regulates phosphatidylcholine translocator ABCB1 (ABCB1B), canalicular multispecific organic anion transporter 1 (ABCC2), cytochrome P450 4A2 (CYP4A2), cytochrome P450 1A1 (CYP1A1), cytochrome P450 1A2 (CYP1A2), estrogen receptor (ESR1), and DNA topoisomerase 2-alpha (TOP2A), inhibits oxidative stress, apoptosis, and inflammatory responses, and accelerates drug metabolism. In this study, we provide the investigation of the efficacy of GC against CP-induced hepatotoxicity, and offers a promising alternative for the clinic.